2021
DOI: 10.1177/08465371211056552
|View full text |Cite
|
Sign up to set email alerts
|

Addition of CT to Improve the Diagnostic Confidence for the Detection of Sacroiliac Joint Erosions in Patients with Equivocal MRI Findings

Abstract: Purpose To determine if CT can improve the diagnostic confidence for the detection of sacroiliac joint (SIJ) erosions in patients with equivocal MRI findings. Methods A retrospective analysis of adult patients who had an SIJ MRI and a subsequent SIJ CT within 12 months was conducted. Using a 5-point Likert scale, two reviewers evaluated the de-identified MRI and CT images in randomized order and in separate sessions to answer the question: “Does the patient have SIJ erosions?”. A Fisher’s exact test was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…However, because radiographic changes occur in the later stages of AS, the classification based on the NY criteria is not used to determine the early stages of the disease [ 2 ]. The early stages of the disease include SIJ and spinal inflammation, which is not present on radiographs, while the late stages of the disease include inflammatory and structural changes, which can be seen on radiographs [ 8 ]. Although conventional radiography is the imaging technique of choice for diagnosing SpAs, the oblique and curved contour of the SIJ makes conventional radiography difficult when detecting anatomic changes such as erosions, sclerosis, bony bridges, and ankylosis [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, because radiographic changes occur in the later stages of AS, the classification based on the NY criteria is not used to determine the early stages of the disease [ 2 ]. The early stages of the disease include SIJ and spinal inflammation, which is not present on radiographs, while the late stages of the disease include inflammatory and structural changes, which can be seen on radiographs [ 8 ]. Although conventional radiography is the imaging technique of choice for diagnosing SpAs, the oblique and curved contour of the SIJ makes conventional radiography difficult when detecting anatomic changes such as erosions, sclerosis, bony bridges, and ankylosis [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…The study conducted by Nadeem et al consisted of patients over the age of 18 at a tertiary care center who had an SIJ MRI and then an SIJ CT completed within 12 months, with 14 weeks between the CT and MRI. The results concluded that SIJ CT has greater diagnostic confidence in relation to SIJ MRI [ 8 ]. Further, of the patients that had equivocal findings on MRI, 73.2% had a definitive diagnosis on CT, which demonstrates the increased confidence in detecting the presence of erosions on CTs [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations